PEMIDANAAN PELAKU DI ATAS TUNTUTAN JAKSA PENUNTUT UMUM PADA TINDAK PIDANA PEMBUNUHAN (Studi Putusan Nomor 17/Pid.B/2021/PN.Gst) - Jesika Greis Duha (Jurnal Panah Hukum, 2022)
Murder is an act to eliminate a person's life by violating the law, or not against the law. One of the crimes of murder that has been examined and tried by the Gunungsitoli District Court is decision number 17/Pid.B/2021/PN.Gst. In the decision, the perpetrator was charged with 7 years in prison and violated Article 338 of the Criminal Code with the first alternative charge of Article 351 paragraph (3) of the Criminal Code, while the judge sentenced the perpetrator to 10 years in prison for allegedly violating Article 338 of the Criminal Code. The type of research used is normative legal research with approach methods, namely legislation approach, case approach and analytical approach. Data was collected using secondary data obtained through library materials consisting of primary legal materials, secondary legal materials and tertiary legal materials. The data analysis used is descriptive qualitative analysis and the conclusion is drawn using the deductive method. Based on the research findings and discussion, it can be concluded that the punishment of the perpetrator above the demands of the Public Prosecutor for the crime of murder (Study of Decision Number 17/Pid.B/2021/PN.Gst) is a crime imposed on the demands of the Public Prosecutor, The judge may decide above the demands in accordance with the laws and regulations because there is no provision that prohibits the judge in deciding the sentence of a person to be in accordance with the demands of the Public Prosecutor. In addition, it is not Article 338 of the Criminal Code that is imposed on the perpetrator, but uses the first alternative charge, namely Article 351 paragraph (3) in order to fulfill the elements of the act committed by the perpetrator. The author suggests that judges should pay more attention to the punishment of a person in order to fulfill the elements in an article that is charged to the perpetrator so that the sentence imposed is in accordance with his actions